Endoscopic Resection and Post-Operative Brachytherapy in the Treatment of Sinonasal Melanoma - Alhadad, Abdulrauf I (Division of Otorhinolaryngology, 2020)
Background: Sino-Nasal Melanomas (SNM) are rare, aggressive tumours often associated with a poor prognosis due to advanced stage disease at presentation. Mean 5-year survival is 0-46%. Various treatment modalities are used in the management of SNM. Surgery is regarded as the primary treatment modality, but therapy remains controversial. Complete resection is a surgical challenge and it is often impossible to achieve adequate margins due to the fact that tumour often abuts vital anatomical structures. Incomplete resection has been shown to be a predictor of poor survival. Harris et al. (2014) were the first to report on the use of post-operative brachytherapy in an attempt to prevent local recurrence after endoscopic resection of SNM. Methods: A retrospective analysis of all patients undergoing endoscopic resection of SNMs and receiving adjuvant brachytherapy in a single surgeon’s practice between August 2004 and May 2014 was carried out. Outcome measures included local control rate and 5-year overall survival estimated by Kaplan-Meier analysis. The incidence of regional and distal recurrence (metastases) was calculated Results: Five cases of sinonasal melanoma (3 males 2, females) were managed with endoscopic resection and adjuvant brachytherapy. Patients were followed up for a median duration of 61 months (32-154 months) following adjuvant Brachytherapy. Local control was achieved in four out of five patients (80%). Three out of five patients developed distant metastasis. Median time to metastasis was 54 months. One patient received immunotherapy after diagnosis of distant metastasis (BRAF positive). Three out of five patients (60%) died from the complications of distant metastases of sinonasal melanoma. Median survival time following adjuvant Brachytherapy was 61 months (32-154 months). Five-year survival rate was 40% (95% CI 5.2% - 75.3%). Conclusion: This is the only case series describing the use of brachytherapy following endoscopic resection of sinonasal melanoma. Our case series, albeit small, describes a local control rate and 5-year survival comparable with the best reported in the literature. Adjuvant brachytherapy represents a novel approach and potentially a useful addition to the adjuvant therapy armamentarium. The advantages of brachytherapy include a favourable side-effect profile and a shorter duration of treatment, while delivering a dose of radiation similar to that of Conventional Radiotherapy. Further studies are necessary to define the role of brachytherapy in sinonasal melanoma.